Arbuscular mycorrhizal fungi in heavy metal highly polluted soil in the Riachuelo river basin - Colombo, Roxana (2019)
The Riachuelo river basin (RRB) is considered one of the most polluted environments in the world. Knowledge of arbuscular mycorrhizal fungi (AMF) adapted to this extremely polluted environment is important for the establishment of future soil restoration projects. This work aims to make a first list of AMF species present on the RRB. Soil and root samples were randomly taken in an area of approximately 1500 m2, mycorrhization percentages were evaluated. AMF species were detected by molecular and morphological techniques. Sixteen AMF morphological species and 64 molecular species were reported in this work. Dominikia iranica, Funneliformis constrictum, Funneliformis mosseae, Rhizophagus intraradices, Rhizophagus irregularis and Septoglomus viscosum were detected by both techniques while Claroideoglomus sp. was only detected by pyrosequencing. The list of species reported in this work represents the first description of the RRB AMF community.